2006
DOI: 10.1002/elan.200503391
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Anodic Stripping Voltammetry with Bismuth-Modified Carbon Paste Electrodes

Abstract: In this article, the results of some recent investigations on two types of bismuth-modified carbon paste electrodes are presented. In the first study, the bismuth-film carbon paste electrode (BiF-CPE) operated in situ and employed in anodic stripping voltammetry of Cd(II) and Pb(II) at the low mg L À1 level was of interest in view of choosing the proper Bi(III)-to-Me(II) concentration ratios (where Me: Pb or Cd). Such optimization has resulted in significant improvement of detection limits down to 1.0 mg L À1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
1
12

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(90 citation statements)
references
References 28 publications
(52 reference statements)
3
74
1
12
Order By: Relevance
“…It has been shown that bismuth film electrodes have the same advantages as mercury film electrodes and at the same time, due to the negligible toxicity of bismuth, they are also environmentally friendly. [6][7][8] Various types of bismuth modified electrodes have been utilized for the determination of heavy metals using stripping analysis methods. Bismuth is used for the modification of different kinds of carbon based electrodes such as carbon paste electrodes, 6,9-11 carbon fiber electrodes, 8 graphite epoxy composite electrodes, 12,13 carbon nanotube nanoelectrode array, 14 carbon film electrodes, 15,16 boron doped diamond 17 and particularly glassy carbon electrodes.…”
mentioning
confidence: 99%
“…It has been shown that bismuth film electrodes have the same advantages as mercury film electrodes and at the same time, due to the negligible toxicity of bismuth, they are also environmentally friendly. [6][7][8] Various types of bismuth modified electrodes have been utilized for the determination of heavy metals using stripping analysis methods. Bismuth is used for the modification of different kinds of carbon based electrodes such as carbon paste electrodes, 6,9-11 carbon fiber electrodes, 8 graphite epoxy composite electrodes, 12,13 carbon nanotube nanoelectrode array, 14 carbon film electrodes, 15,16 boron doped diamond 17 and particularly glassy carbon electrodes.…”
mentioning
confidence: 99%
“…Indeed, the optimum Bi 3+ concentration has been evaluated for the complete formation of multi-component alloys, 25 the prevention of a high hydrogen evolution rate at negative potentials and the saturation effect of Bi-film on the surface of CPE. 16,18,26,27 As reported by Švancara et al, 16 the Bi 3+ concentration must be 10 times higher than the target analyte concentration to avoid a saturation effect. Thus, a concentration of 5 mg dm -3 was used as the optimal Bi 3+ concentration in the preparation of the CPE for this in-house designed thin-layer flow cell.…”
Section: Effect Of Bismuth Concentrationmentioning
confidence: 80%
“…Bismuth electrodes have been successfully applied in anodic [20][21][22] and cathodic or adsorptive stripping voltammetry (AdCSV) [23,24]. The latter technique relies on the interfacial accumulation of a complex of the target metal on the surface of the working electrode; this is an interesting approach, especially when the analyte cannot form an amalgam/alloy [25][26][27].…”
Section: Introductionmentioning
confidence: 99%